Peace love yoga : the politics of global spirituality - Jain, Andrea R. (New York, NY : Oxford University Press, 2020)
"In Peace Love Yoga, Jain analyses growing spiritual industries and their coherence with neoliberal capitalism. "Personal growth," "self-care," and "transformation" are just some of the generative tropes in the narrative of these industries. Jain illuminates the power dynamics underlying what she calls neoliberal spirituality, illustrating how spiritual commodities are rooted in concerns about deviancy, not only in the form of low productivity but also forms of social deviancy. Jain, however, does not just offer one more voice bemoaning the commodification of spirituality as a numbing device through which consumers ignore the problems of neoliberal capitalism or as the corruption or loss of "authentic" religious forms. Instead, she asks what we should make of subversive spiritual discourses that call on adherents to think beyond the individual and even out into the environment, claims to counter the problems of unbridled capitalism with charitable giving or "conscious capitalism," challenges to the imperialism behind the appropriation and commodification of products from yoga to mindfulness, calls for women's empowerment, and efforts to greenwash commodities, making them more environmentally "friendly" or "sustainable." Rather than a mode through which consumers ignore, escape, or are numbed to the problems of neoliberal capitalism, many spiritual commodities, corporations, and entrepreneurs, Jain suggests, do actually acknowledge those problems and, in fact, subvert them; but they subvert them through mere gestures. From provocative taglines printed across t-shirts or packaging to calls for "conscious capitalism," commodification serves as a strategy through which subversion itself is contained"--
Includes bibliographical references (pages 179-202) and index.
Keywords: Spirituality